The importance of being heard: Stories of unrepresented litigants in small claims cases and private family proceedings - Grieshofer, Tatiana (Language and Law / Linguagem e Direito, 2022)
The article explores narrativisation practices in small claims cases and private family proceedings, focusing predominantly on cases where at least one of the parties is not represented by a lawyer. By drawing on the data collected during court observations and analysed using the ethnography of communication as the main methodological framework, the study identifies narrative genres across different stages of legal proceedings and illustrates communication barriers experienced by lay court users. The discussion focuses on how formalised narrative genres and the staggered presentation of narratives impact the degree to which court users can use their voice. The article also links the notion of voice projection to procedural justice and suggests that the main narratives should be elicited sooner as part of an open narrative strategy to ensure the court users’ voices are heard by the judiciary in the initial stages of the proceedings.